(untitled) (Revista da Faculdade de Medicina Veterinária e Zootecnia da Universidade de São Paulo, 1977)
The A.A. studied the length of the various enteric tracts as well as their full length in 40 adult zebu cattle (20 males and 20 females) and achieved the following overage, once there was no significant difference concerning sex: thin intestine.................................31.15 ± 2.73 caecun............................................0.51 ± 0.11 colon and rectun.............................. 6.80 ± 0.80 gross intestine................................. 7.31 ± 0 .7 5 full length.......................................38.84 ± 3.26 On the other hand, there was no correlation between the full length of the intestine and the weight or length of the carcasses.